Interventional Magnetic Resonance Imaging - Kahn, Thomas; Busse, Harald; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Magnetic resonance imaging (MRI) has become one of the most powerful diagnostic tools in modern medicine, with a number of well-known advantages in terms of image quality, functional imaging options, and patient safety. The idea of using this enormous potential also for interventional purposes may seem obvious, but it took major efforts by engineers, physicists, and clinicians to come up with dedicated interventional techniques and scanners, and improvements are still ongoing. Since the inception of interventional MRI in the mid-1990s, the numbers of settings, techniques, and clinical applications have increased dramatically. This state of the art book covers all aspects of interventional MRI. The more technical contributions offer an overview of the fundamental ideas and concepts and present the available instrumentation. The richly illustrated clinical contributions, ranging from MRI-guided biopsies to completely MRI-controlled therapies in various body regions, provide detailed information on established and emerging applications and identify future trends and challenges.
Systems for Interventional MRI -- Pulse Sequences for Interventional MRI -- RF Coils for Interventional MRI -- Instruments for Interventional MRI -- Safety Considerations in Interventional MRI -- Anesthesia Management -- MRI Guidance of Minimally Invasive Cranial Applications -- Intracranial Tumor Resections -- Nonneoplastic Neurosurgical Applications -- MRI-Guided Biopsies -- Navigation Techniques for MRI-Guided Interventions -- Robotic Devices -- MRI-Guided Musculoskeletal Interventions -- Breast Interventions -- Thermal Ablation Techniques -- Laser Ablation in the Brain -- Laser Ablation in the Liver -- RF Ablation in the Liver -- RF Ablation in the Kidney -- HIFU of Uterine Fibroids -- HIFU in the Liver and Kidney -- HIFU in the Brain -- Brachytherapy in the Liver -- Microwave Ablation -- Cryoablation in Open MRI Scanners -- Wide-Bore MRI Scanners -- MRI Guidance of Vascular Applications -- Cardiac Applications -- MRI-Guided Prostate Biopsies -- Therapeutic Procedures in the Prostate -- Targeted Drug Delivery -- Stem Cell Therapy -- Delivery and Tracking of Cellular Therapeutics -- Hybrid MRI Systems and Applications -- Simultaneous Ultrasound and MRI Acquisition -- Simultaneous Endoscopy and MRI Acquisition.
Keywords: Medicine; Radiology; Interventional radiology; Oncology; Physical measurements; Measurement; Medical physics; Radiation; Medicine & Public Health; Imaging / Radiology; Interventional Radiology; Diagnostic Radiology; Oncology; Medical and Radiation Physics; Measurement Science and Instrumentation; Electronic books